Pinpointing the Determinants of Financial Literacy: Empirical Evidence of Indonesian Employees in Malaysia - Rizal, Achmad; Susilo, Adib; Rahman Abadi, M. Kurnia; Lahuri, Setiawan; Abdullah, Nurdianawati Irwani; Che Embi, Nor Azizan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
This paper investigates the determinants variables of financial literacy through Exploratory Factor Analysis among Indonesian employees’ works in Malaysia. This study is quantitative study with 117 respondents. The data from respondents are collected through questionnaire on five-point Likert scale. Data analysis employs EFA (Exploratory Factor Analysis) which reduce the factors into expected variables. The study found that there 7 factors emerged in based on data analysis namely, financial literacy contributes with higher percentages factors 13.93%, financial planning contributes with 11.28%, financial control with 9.86%, exchange rate awareness with 9.52%, financial attitude with 9.07, financial subjective norms with 8.76, and lastly financial awareness contributes 6.93%. Meanwhile, simultaneously all variables have commutative percentages about 69.38%. Further studies are required to investigate or examine each emerged variables for example, SEM, Regression analysis, One Way ANOVA, and so on. Moreover, wider coverage of research sample and research object also suggested.